2021
DOI: 10.1038/s41531-021-00232-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain and α-synuclein RT-QuIC as differential diagnostic biomarkers in parkinsonisms and related syndromes

Abstract: Neurofilament light chain (NfL) and α-synuclein oligomeric seeds (α-syn-s) are promising biomarkers for patients with parkinsonism. We assessed their performance in discriminating Parkinson disease (PD) from atypical parkinsonisms (APDs) and evaluated the association between NfL levels and clinical measures of disease severity. We measured NfL in cerebrospinal fluid (CSF) and/or plasma by immunoassays and α-syn-s in CSF by real-time quaking-induced conversion (RT-QuIC) in patients with PD (n = 153), multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 42 publications
(45 reference statements)
4
60
0
Order By: Relevance
“…Similarly, the association of α-syn SAA positivity with increased CSF levels of neurofilament light chain (NfL), a well-established marker of axonal degeneration, may indicate a synucleinopathy in which neurodegeneration is relevant, which is more suggestive of MSA, rather than PD. 24,44 Indeed, in a recent investigation, Quadalti et al 44 demonstrated that the measurement of CSF NfL significantly increased the ability of α-syn SAA in differentiating PD from MSA and PD from PSP/CBS.…”
Section: Road Toward α-Syn Saas Clinical Implementationmentioning
confidence: 99%
“…Similarly, the association of α-syn SAA positivity with increased CSF levels of neurofilament light chain (NfL), a well-established marker of axonal degeneration, may indicate a synucleinopathy in which neurodegeneration is relevant, which is more suggestive of MSA, rather than PD. 24,44 Indeed, in a recent investigation, Quadalti et al 44 demonstrated that the measurement of CSF NfL significantly increased the ability of α-syn SAA in differentiating PD from MSA and PD from PSP/CBS.…”
Section: Road Toward α-Syn Saas Clinical Implementationmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a highly prevalent neurodegenerative disorder worldwide with characteristic motor dysfunctions including bradykinesia, stiffness and resting tremor ( Tolosa et al, 2021 ). Ours and other studies have indicated that some indicators such as neuroinflammatory, neuroimaging mediators and serum neurofilament light chain are usually applied as markers in diagnosing and evaluating the progression and severity of PD and PD Syndromes ( Wang et al, 2020 , 2021 ; Yang et al, 2020 ; Zhu et al, 2020 , 2021a ; Bestwick et al, 2021 ; Liu et al, 2021 ; Quadalti et al, 2021 ). Identifying potential biomarkers for early diagnosis and assessment is one of the research hotspots in the field of PD ( Avenali et al, 2020 ; Papuć and Rejdak, 2020 ; Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of seed amplification assays that identify the underlying proteinopathy together with other biomarkers, for example, neurofilament light chain as a measure of neuroaxonal breakdown, have the potential to further improve diagnostic accuracy. For example, in one recent study typical α-synuclein seeding activity on RT-QuIC distinguished PD from MSA, CBD, and PSP with a sensitivity of 91.4% and specificity 97.5%, whereas a combination of α-synuclein RT-QuIC positivity and NfL below a certain threshold achieved a sensitivity of 98.3% and specificity of 95.8% and a greater area under the receiver operating characteristic curve (Quadalti et al, 2021 ). With recent advances in ultrasensitive, high-throughput protein detection and commercial availability of plasma proteomics panels incorporating thousands of proteins, we anticipate progress in combinatorial approaches in which proteopathic seed identification could be combined with signatures of plasma protein alterations to improve diagnostic and prognostic classification, with potential for enrichment of clinical trials with patient subgroups most likely to benefit from specific treatments (Assarsson et al, 2014 ; Olink, 2021 ).…”
Section: Role Of Protein Aggregation With Seed Amplification Assays I...mentioning
confidence: 99%
“…One report of good diagnostic accuracy in slow IPD with RT-QuIC using recombinant human PrP substrate (Sano et al, 2013 Rossi et al (2020). In a different study aiming to distinguish PD and atypical Parkinsonian disorders, RT-QuIC was negative in all PAF patients (Quadalti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%